Defining embryonic developmental effects of chemical mixtures using the embryonic stem cell test. (June 2020) - van Oostrom, Conny TM.; Slob, Wout; van der Ven, Leo TM.
Abstract: The embryonic stem cell test (EST) was applied to evaluate dose addition in combined exposures of teratogenic compounds in the EFSA-defined cumulative assessment group "craniofacial malformations", which was one of the selected cases in the EU-H2020 project "EuroMix". Test compounds were selected through reported effects in rodents, and represented a wide variety of chemical families and modes of action (MOA), including triazoles to inhibit CYP26; (synthetic) retinoids, to activate RAR/RXR; valproic acid, to inhibit histone deacetylase; dithiocarbamates, to disrupt extracellular matrix formation; dioxin (-like) compounds, to activate the aryl hydrocarbon receptor; 17alpha-ethynylestradiol, to activate the estrogen receptor; 5-fluorouracil, to disrupt DNA-synthesis; MEHP and PFOS, to activate peroxisome proliferation activated receptors; and methyl mercury, to induce oxidative stress and inhibit protein function. The EST appeared particularly useful to evaluate differentiation-inhibiting effects of compounds targeting early processes in craniofacial development, possibly related to the early fate of neural crest cells. Mixtures, designed as equipotent concentrations of two compounds with similar or dissimilar MOA, and single compounds showed overlapping dose-responses. This observation is consistent with dose addition in the EST in all studied binary mixtures, irrespective of MOA, and thereby supports the application of dose-addition as a default in cumulative risk assessment.